2011
DOI: 10.1016/j.neuroscience.2011.01.046
|View full text |Cite
|
Sign up to set email alerts
|

Role of neurotrophins on postnatal neurogenesis in the thalamus: prenatal exposure to ethanol

Abstract: A second wave of neuronal generation occurs in the ventrobasal nucleus of the rat thalamus (VB) during the first three postnatal weeks. The present study tested the hypotheses (1) that postnatal neurogenesis in the VB is neurotrophin-regulated and (2) that ethanol-induced changes in this proliferation are mediated by neurotrophins. The first studies examined the effects of neurotrophins on the numbers of cycling cells in ex vivo preparations of the VB from three-dayold rats. The proportion of cycling (Ki-67-po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 83 publications
0
8
1
Order By: Relevance
“…It has been shown that prenatal and adult chronic EtOH exposure alters levels of neurotrophin, such as brain derived neurotrophic factor (BDNF), in the frontal cortex and hippocampus (Miller et al, 2002; Davis, 2008; Nixon and McClain, 2010; Mooney and Miller, 2011; Vedder et al, 2015). However, few studies have assessed neurotrophin expression after adolescent CIE and the results are variable (Briones and Woods, 2013; McClain et al, 2014; Sakharkar et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that prenatal and adult chronic EtOH exposure alters levels of neurotrophin, such as brain derived neurotrophic factor (BDNF), in the frontal cortex and hippocampus (Miller et al, 2002; Davis, 2008; Nixon and McClain, 2010; Mooney and Miller, 2011; Vedder et al, 2015). However, few studies have assessed neurotrophin expression after adolescent CIE and the results are variable (Briones and Woods, 2013; McClain et al, 2014; Sakharkar et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In line with these observations, expression of the mature form of brain-derived neurotrophic factor (BDNF) protein has been demonstrated to be elevated at time points when specific brain regions are less sensitive to the deleterious effects of ethanol, such as the cortex at postnatal day (P) 21 and the striatum at P14 (Heaton, Paiva, Madorsky, Mayer, & Moore, 2003). BDNF protein levels have also been shown to be increased in the hippocampus after neonatal ethanol exposure (Heaton, Mitchell, Paiva, & Walker, 2000), suggesting a protective role for BDNF (Lindvall, Kokaia, Bengzon, Elmér, & Kokaia, 1994) in addition to its role in both synaptic plasticity (Chapleau, Larimore, Theibert, & Pozzo-Miller, 2009) and dendritic development via its receptor, tropomyosin-related kinase B (TrkB), a member of the receptor tyrosine kinase family (Mooney & Miller, 2011; Yacoubian & Lo, 2000). Interestingly, BDNF mRNA does not appear to be present in the striatum of embryonic or neonatal mice (Baquet, Gorski, & Jones, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…BDNF is greatly expressed in forebrain and diencephalon throughout normal development (Schmidt-Kastner et al, 1996, Lush et al, 2005, Webster et al, 2006). Cortex-derived BDNF is necessary for thalamic axonal outgrowth and target identification (Lotto et al, 2001), but not for thalamic neurogenesis (Mooney and Miller, 2011). The influence of BDNF in remote areas (e.g.…”
Section: Introductionmentioning
confidence: 99%